Analisis Implementasi Strategi Pemasaran Digital dengan Pendekatan Model SOSTAC di Universitas Putera Batam - Tussi Sulistyowati; Nur Elfi Husda (LPPM Universitas Putera Batam, 2023)
Digital marketing has become a crucial element in the marketing strategy of higher education institutions. This research, adopting a qualitative descriptive research approach and conducted on September 2-3, 2023, aims to provide an in-depth understanding of the practical application of the SOSTAC Model within the framework of Universitas Putera Batam. The research results indicate that the social media performance of Universitas Putera Batam is excellent. On YouTube, there are 428 videos ranking first in terms of video content quantity, along with 1,970 subscribers ranking third among private universities in the Riau Islands. On Instagram, there are 2,887 posts and 11,400 followers, while the Facebook account has 7,500 likes and 7,900 followers, demonstrating excellent performance across all platforms. To enhance engagement, Universitas Putera Batam can take several strategic steps. On the YouTube channel, they can create more informative content that piques the interest of prospective students, such as admission announcement videos. On Instagram, the focus can be directed towards increasing the number of likes by organizing contests or campaigns involving followers to boost engagement. Meanwhile, on Facebook, it is crucial to respond promptly to comments and follower messages and consider sharing more diversified content to improve user interaction. By leveraging the SOSTAC Model and continuously monitoring digital media performance, Universitas Putera Batam can maximize the impact of digital marketing strategies in achieving marketing goals and maintaining attractiveness in the competitive higher education market.